Effect of Plant Growth Regulator on Red Onion Cultivation from True Seed Shallot (TSS) - Tri Sudaryono (Graduate Program, 2018)
Red onion is one of the strategic horticultural commodities, considering this commodity is very high consumption as a daily spice and fluctuating price. Therefore is not surprising that these commodities are contributing to inflation. Efforts to meet increasing consumption needs, it is necessary to find the right strategy to increase domestic red onion production. One of the strategies considered to increase domestic red onion production is the use of botanical seed (TSS) as a source of seed on shallot cultivation. There are 2 main weaknesses of red onion cultivation with TSS as a source of seeds. The two weaknesses are TSS low growing power, which is naturally only in the 50-60 % range and the number of tubers produced is less than 3 cloves per plant. In order to solve the problem, research has been done to know the effect of plant growth regulator on the growth and red onion production from TSS and also get the description of red onion farming from TSS and tuber as seed source. The research was conducted from June to November 2017 at BPP Pare, Kediri Regency, East Java. The results showed that the use of young coconut water on TSS obtained red onion plants are able to produce the number of tubers per plant more than 3 cloves. In detail as much as 22.22 % produces the number of tubers range 4-5 per plant; 56.56 % yields 5-6 bulb range; and as much as 22.22 % produces tubers > 6. As well, wet weight of tubers when harvested weighing more than 99 g per plant. If converted per hectare, TSS red onion plants treated with young coconut water can produce a range of 30 -35 tons of wet bulb. This production is doubled compared to the production of shallots grown from tubers. Based on the analysis of the farm, red onion from TSS treated with young coconut water gives a profit of Rp 224,860,000 per hectare with B/C ratio of 3.397. This profit is more than 1.75 times compared to the profit of red onion tuber farming which is only Rp 93.787.000, - with B/C ratio of 1,061.Keywords: Farming Analysis, Growing Power, Growth, Red Onion, TSS, Yield